The Development Ceramic Glaze from Waste Materials in Sakon Nakhon Local Textile Handicraft’s - Khampilar, Nutcharath (Journal of Fine and Applied Arts Khon Kaen University, 2024)
The purpose of this research is to study the leftover materials from Sattha Pha Indigo Province. Sakon Nakhon and then developed it into a ceramic glaze by conducting research in 2 steps. Step 1: Studying waste materials from indigo handicrafts, and Step 2: Experimenting with developing glaze from waste materials. By selecting specifically from the experimental mixture formula in linear theory. Fired at a temperature of 1,230 degrees Celsius, glazed on a stoneware clay test rod, code PBG, Compound Clay Company. In an oxidation firing and reduction firing, sock on fire for 15 minutes at a temperature of 1,230 degrees Celsius. In indigo handicrafts, it was found that the most waste materials were Indigo plant from fermentation to make indigo meat Therefore it was firing to become ashes. To be the main raw material for developing ceramic glazes. The results of the experiment found that The most complete glaze In both sets of experiments, Formula 6 had a mixture of 50 percent indigo ash and 50 percent kaolin. The glaze had good melted . Has good adhesion to the glaze test rod. in oxidation firing. This gives the glaze Light brown clear glazed and there are many dark brown spots scattered on the glaze. It is smooth and has a small surface. In reduction firing. This gives the glaze a light bluish-green color. There are orange-brown spots on the glaze. Around the bottom edge, orange vapor appears around the base of the glaze. It does not flow. And formula number 7 has a mixture of 40 percent indigo ash and 60 percent kaolin. The glaze is melted . Good adhesion to the glaze test stick. In oxidation firing, light brown. and has dark brown spots Spreads moderately on the glaze surface. And in the reduction firing, the glaze has a clear, light blue-green color. There are small and medium sized light brown spots alternating with dark brown. Spread on the glazed surface The coating is smooth and has small blemishes. Around the bottom edge, a light orange vapor appears around the base of the glazed. The glaze does not flow. And next is formula number 5, a mixture of 70 percent indigo ashes and 30 percent kaolin clay. The glaze has melted . Good adhesion to the glaze test stick. In an oxidation firing , the glazed is clear, light brown, and has dark brown spots. Spreads moderately on the glazed surface. The glazed surface is smooth and even. There is a small blemish on the skin. In the reduction firing, the coating is clear, light blue-green. There are light brown-orange spots alternating with brown. Spread on the glazed surface The glazed has a small cracked surface. The surface of the glazed is slightly rough. Around the bottom edge, orange vapor appears around the base of the glazed. The glazed mentioned above are most suitable for use in decorating pottery.